How do Small Firms Respond to Tax Schedule Discontinuities? Evidence from South African Tax Registers - Wian Boonzaaier; Jarkko Harju; Tuomas Matikka; Jukka Pirttilä (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the responsiveness of small and medium-sized firms to a small-business corporate income tax schedule using population-wide administrative data from South Africa. We find sizeable bunching of firms at the corporate income thresholds where the corporate tax rate increases, implying active responses to corporate income taxes. The observed bunching is very sharp, and reacts immediately to changes in the location of the kink points. These observations suggest that a sizeable part of the response is driven by reporting responses rather than real economic behavior. We find indicative evidence that reporting behavior is linked to underreporting of sales and legal tax-planning activities.
Keywords: H21; H25; H32; O12; 330; corporate taxation; small firms; emerging economies; bunching